Mild malformation of cortical development with oligodendroglial hyperplasia and epilepsy (MOGHE): a widespread disease with an apparently focal epilepsy. Issue 2 (15th June 2021) - Seetharam, Raghavendra; Nooraine, Javeria; Mhatre, Radhika; Ramachandran, Jaychandran; Iyer, Rajesh B.; Mahadevan, Anita
Abstract: Mild malformation of cortical development with oligodendroglial hyperplasia and epilepsy (MOGHE) is a recently recognized, highly epileptogenic, distinct histopathological entity in drug‐resistant epilepsy that primarily involves the frontal lobes. Surgical outcomes in MOGHE are variable. Although the diagnosis is based on histopathology, high‐resolution MRI helps to differentiate MOGHE preoperatively from other forms of cortical malformations ( i.e ., mMCD II and FCD IIa). We discuss the clinical, electrographic, radiological and histopathological characteristics of MOGHE in two patients who underwent evaluation for drug‐resistant epilepsy followed by electrocorticography‐based resection. Both patients presented with childhood‐onset refractory frontal lobe epilepsy with a high seizure burden. Interictal epileptiform discharges were widespread. PET abnormalities were disproportionate to the MRI findings. Cognitive impairment, persistent epileptiform discharges on post‐resection electrocorticography and sub‐optimal surgical outcomes suggest that MOGHE is a widespread pathology in focal epilepsy.